Polyphony. Polish, Czech and Slovak Texts about the Holocaust - Piotrowiak-Junkiert, Kinga (Poznańskie Studia Slawistyczne, 2023)
Handbook of Polish, Czech, and Slovak Holocaust Fiction. Eds. Elisa-Maria Hiemer, Jiří Holý, Agata Firlej, Hana Nichtburgerová. Berlin: De Gruyter. 2021, 514 s. DOI: https://doi.org/10.1515/9783110671056